Organogenesis Tanaman Bawang Merah (Allium ascalonicum L.) Menggunakan Umbi Secara In Vitro pada Media Dasar Murashige and Skoog yang Diperkaya Vitamin B5 dengan Naftalene Acetic Acid dan 6-Benzyl Amino Purine - NOVIANITA, KATARINA IKA; SRITAMIN, MADE; ADIARTAYASA, WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.8, No.3, Juli 2019, 2019)
Organogenesis of Shallot Plant ( Allium ascalonicum L.) Using Shallot Bulb with In Vitro Method on Murashige and Skoog Basic Media that Enriched by Vitamin B5 with Naftalene Acetic Acid and 6-Benzyl Amino Purine   This study was conducted to determine the effect of the combination of NAA ( Naftalene Acetic Acid ) and BAP ( 6-Benzyl Amino Purine ) in MS media which can stimulate organogenesis in the onion ( Allium ascalonicum L.) Biru Lancor variety in vitro. This experiment used four treatments, namely P1 (NAA 1 mg / L + BAP 2 mg / L), P2 (NAA 2 mg / L + BAP 2 mg / L), P3 (Vitamin B5 + NAA 1 mg / L + BAP 1) mg / L), and P4 (Vitamin B5 + NAA 2 mg / L + BAP 2 mg / L). Based on observations made on the growth and development of onion bulbs in vitro, treatment P3 with the combination of concentration 1 mg / L NAA and 1 mg/L BAP with the addition of vitamin B5 can stimulate organogenesis well to the number of leaf shoots, leaf length, number of roots and root length. This media provides the best results for the observed parameters compared to other treatments.